PHYLOGENETIC RELATIONSHIP OF SELECTED PAKISTANI WHEAT VARIETIES BASED ON A CHLOROPLAST RPS11 GENE - S. Rehman; H. J. Chaudhary; A. Rasheed; T. Mahmood (Journal of Animal and Plant Sciences, 2015)
Wheat (Triticum aestivum L.) is a major crop among all cereals and consumed in major parts of the world as a staple food. The assessment of genetic diversity in wheat is of prime importance for conservation, breeding programs and to broaden the genetic makeup to develop high quality varieties. The present study aimed at the evaluation of evolutionary divergence pattern and genetic relationship among eight selected Pakistani wheat varieties based on a chloroplast gene. To achieve the main objective, rps 11 gene was amplified, sequenced and analyzed with the help of Bioinformatics tools. The constructed MEGA 5 phlogenetic tree revealed considerable level of genetic similarity among studied varieties with overall genetic distance of 0.05. The evolutionary divergence data based on pair wise distance analysis identified Chakwal-50 and Watan as most diverse varieties among all selected varieties. Phylogenetic relationship and genetic diversity concluded in this study based on rps 11 gene can be reliably used for assessing genetic kinship among wheat cultivars and to possibly change the direction of breeding programs in future.
Keywords: Genetic diversity; Phylogenetic analysis; Pair wise distance